2006
DOI: 10.1111/j.1541-4337.2006.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance: Implications for the Food System

Abstract: The safety of food worldwide remains challenged by the potential for emergence of new pathogens and re‐emergence of known pathogens. Microorganisms have an inherent ability to evolve—to mutate and adapt to environmental stressors—allowing them to survive otherwise lethal conditions. The Institute of Food Technologists (IFT),1 the 22000‐member nonprofit scientific and educational society, convened a panel of internationally renowned experts to address the concern that the use of antimicrobials in food productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(15 citation statements)
references
References 583 publications
(593 reference statements)
0
15
0
Order By: Relevance
“…Based on these findings, resistant to penicillin and ampicillin could be probably due to extensively used of antibiotics in aquaculture and the impact of antimicrobial residues in aquatic systems. It is also likely due to the complexity of the Gram-negative bacteria outer membrane which inhibits antibiotic compounds to pass through the outer membrane (IFT, 2006; Blair et al, 2014). Penicillin and ampicillin are therefore ineffective for the treatment of V. parahaemolyticus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, resistant to penicillin and ampicillin could be probably due to extensively used of antibiotics in aquaculture and the impact of antimicrobial residues in aquatic systems. It is also likely due to the complexity of the Gram-negative bacteria outer membrane which inhibits antibiotic compounds to pass through the outer membrane (IFT, 2006; Blair et al, 2014). Penicillin and ampicillin are therefore ineffective for the treatment of V. parahaemolyticus infections.…”
Section: Discussionmentioning
confidence: 99%
“…It could also occur through the acquisition of mobile extrachromosomal DNA elements including transposons, integrons, and plasmids instead of mutation. The acquisition of the genes that code for Beta-lactamase (the enzyme responsible for the cleavage of Beta-lactam antibiotics, such as cephalosporins and penicillins), is an example of acquired resistance (Doyle et al, 2006). Transformation happens when bacteria pick up free DNA containing the resistance genes from the environment; transduction occurs when DNA carrying the resistance genes is transferred via bacteriophages, which are viruses that affect bacteria; and conjugation takes place when the genes are transferred via conjugative pili (Roca et al, 2015).…”
Section: Molecular Development and General Mechanisms Of Antibioticmentioning
confidence: 99%
“…The inherent utility and practical applications of plant extracts such as garlic, cinnamon, tulsi, ginger, turmeric, lemon, neem, yucca, thyme and rosemary have been explored for improving poultry health as well as production with fruitful results [17, 18]. Though, it has been reported that some plant based chemotherapeutic agents may be ineffective on emerging resistant bacterial strains [19, 20], therefore, further work still needs to be done to search for more effective plant based chemotherapeutic agents especially for poultry chicken management.…”
Section: Introductionmentioning
confidence: 99%